Performance of laying pullets fed microbial combinations up to eighteen weeks of age/ the age of sexual maturity - SHARMA, K S; SHARMA, V K; KUMARI, M; KATOCH, SHIVANI; KAISTHA, MUKUL; KATOCH, B S (The Indian Journal of Animal Sciences, 2014)
Comparative dietary response of the combinations of different strains of lactobacilli, streptococci and yeast isolated from indigenous sources was studied in commercial egg type chicken, Various treatments consisted of T1 (control culture medium), T2 (Lactobacillus bulgaricus L4 + Streptococcus lactis SI +Saccharomyces cerevisiae Y3), T3 (L. plantarum carrot + S. jaecium onion + S. cerevisiae crow), T4 (L. salivarlus cauliflower + S.faecium banana + S. cerevisiae food yeast), T5 (L. acidophillus leopard + S feacalis leopard + Tornlopsis spherica calf) and T6 (L. acidophillus bottle gourd + S. uberis bitter gourd + S, cerel’isiae bitter gourd). During the starter phase the gain in weight (GIW) was higher (P<0.05) in all the treatment groups as compared to T1, and the feed efficiency ratio (FER) was better in T6, T5, T4 and T3 as compared to T2 and T1. During the grower phase the GIW and FER were better in T4, T6 and T5 as compared to T3, T2 and TI treatments which was because of their significantly higher GIW and lower feed consumption. The trend of overall perfomlance from 1-18 weeks of age was the same as was observed during the grower phase. The egg laying perfomlance for 12 months was better in T5 and T6 as compared to all others. The overall growth and egg laying performance also seemed to be linked to total and differential microbial counts in the small intestines and excreta under different treatments. The microbial combinations fed up to only grower phase were well established in the gastrointestinal tract of birds eliciting their beneficial effects throughout the laying period.